1966
DOI: 10.1126/science.154.3756.1583
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Diameter and Load on Memory

Abstract: During a short-term memory task, pupil diameter is a measure of the amount of material which is under active processing at any time. The pupil dilates as the material is presented and constricts during report. The rate of change of these functions is related to task difficulty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

82
1,075
5
6

Year Published

1975
1975
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,344 publications
(1,168 citation statements)
references
References 6 publications
82
1,075
5
6
Order By: Relevance
“…According to the Cognitive Load model of Kahneman and Beatty (Beatty, 1982;Kahneman & Beatty, 1966;Kahneman, 1973), pupil dilation is a peripheral marker of arousal that serves to transiently increase cognitive capacity as a result of either the 'voluntary' or 'involuntary' deployment of attention. When voluntary, the subject chooses to engage in a problem or decision task and the inherent 'top-down' demands of the task drive both the level of cognitive effort and pupillary dilation (Kahneman, 1973).…”
Section: The Cognitive Load Model and Its Prior Application To The Pumentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Cognitive Load model of Kahneman and Beatty (Beatty, 1982;Kahneman & Beatty, 1966;Kahneman, 1973), pupil dilation is a peripheral marker of arousal that serves to transiently increase cognitive capacity as a result of either the 'voluntary' or 'involuntary' deployment of attention. When voluntary, the subject chooses to engage in a problem or decision task and the inherent 'top-down' demands of the task drive both the level of cognitive effort and pupillary dilation (Kahneman, 1973).…”
Section: The Cognitive Load Model and Its Prior Application To The Pumentioning
confidence: 99%
“…When voluntary, the subject chooses to engage in a problem or decision task and the inherent 'top-down' demands of the task drive both the level of cognitive effort and pupillary dilation (Kahneman, 1973). For example, in a working memory digit span task, pupil dilation increases as the number of digits to be retained also increases (Kahneman & Beatty, 1966), tracking the greater effort expended for the larger memory set size. Critically, under voluntary attention, increasingly effortful tasks should yield increasingly slowed, erroneous and uncertain responding (Kahneman, 1973).…”
Section: The Cognitive Load Model and Its Prior Application To The Pumentioning
confidence: 99%
See 1 more Smart Citation
“…Hess & Polt, 1960), cognitive load (Kahneman & Beatty, 1966), and mental effort (Kahneman, 1973;Hess & Polt, Sequential action representation in infancy 15 1964). Whatever the exact interpretation of the measure, using it enables us to contrast acquisition contingent vs. non-contingent responses since all interpretations suggested that dilations should be larger for actions that require more processing (Verschoor et al, in press).…”
Section: Experimental Approachmentioning
confidence: 99%
“…For example, as individuals are asked to remember larger number of digits, for example, pupil dilation increases proportionally (e.g. Kahneman and Beatty, 1966;Granholm et al, 1996). Thus, the pupil has been shown to reflect the time course of activity in brain areas associated with cognitive processing such as the dorso-lateral prefrontal cortex (Siegle et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%